Rheological and structural characterisation of whey protein acid gels co-structured with chia (Salvia hispanica L.) or flax seed (Linum usitatissimum L.) mucilage. (April 2019) - Soukoulis, Christos; Cambier, Sébastien; Serchi, Tommaso; Tsevdou, Maria; Gaiani, Claire; Ferrer, Pau; Taoukis, Petros S.; Hoffmann, Lucien
Abstract: The effects of different plant seed mucilage (PSM) extracts, namely chia seed (CSM) and flaxseed (FSM), on the kinetics of δ-glucono-lactone induced acidification and gelation phenomena of whey proteins (5% w/w WPI) were investigated. The rheological and microstructural properties of mixed whey protein-PSM (0.05–0.75% w/w) cold-set gels produced at 30 or 37 °C were studied by means of oscillatory rheology and confocal microscopy. On exceeding 0.125% of PSM, a significant reduction of the gelation time due to the formation of loosely entangled whey protein soluble aggregates was observed. The impact of PSM on the gelation rates was closely related to the PSM type and concentration. CSM addition induced a gradual reduction of maximal gelation rate over the entire concentration range tested. On the other hand, FSM conferred a steep impedance of the gelation when exceeded 0.375%, which was associated with the occurrence of segregative phase separation. Fitting the elastic modulus – gelation time data to a model adapted to the Flory-Stockmayer theory, it was demonstrated that the presence of PSM inhibits the whey protein crosslinking capacity under both tested acidification regimes, leading to the formation of shorter protein crosslinks and therefore, to lower gel stiffness. However, the formation rate of elastically active chain networks was found to be increasing for CSM and FSM contents up to 0.5 and 0.25% respectively, suggesting a synergistic acid gel structuring effect of PSM under these conditions. Graphical abstract: Highlights: Study of chia (CSM) and flax (FSM) seed mucilage as structurants of WPI acid gels. CSM and FSM reduced gelation rate and hampered whey proteins crosslinking ability. At low concentrations, PSMs enhanced gels stiffness via associative interactions with the protein aggregates. Excess of CSM promoted gels stiffness via steric stabilisation of protein aggregates. Above 0.375%, FSM decreased gels' stiffness due to segregative phase separation.